Implementasi Kebijakan Kompensasi Internasional dan Dampaknya terhadap Kepuasan Kerja Ekspatriat - Deci Aulia Kristina Mangunsong; Chessa salwa Hamidah; Zahrilla Ramadhini; Robert Tua Barasa (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
The increasing deployment of expatriates in multinational corporations highlights the strategic role of international compensation in shaping job satisfaction and assignment success. Despite extensive discussions, prior studies often present fragmented findings and limited synthesis regarding how compensation components influence expatriate experiences across diverse contexts. Using a qualitative literature review approach, this paper systematically analyzes selected scholarly sources published within the last decade, complemented by seminal theories in international human resource management. The analysis focuses on key compensation elements, including base salary, cost-of-living allowances, housing benefits, healthcare coverage, and non-financial support such as cross-cultural training and family assistance. The findings indicate that a well-structured and context-sensitive compensation package significantly contributes to expatriate job satisfaction, particularly when aligned with host-country conditions and individual expectations. However, evidence also reveals that compensation alone is insufficient to ensure satisfaction, as organizational support, work environment, and work–life balance play mediating roles. Additionally, internal equity issues between expatriates and local employees may generate unintended organizational challenges. The study contributes by offering an integrative perspective that connects financial and non-financial compensation dimensions within a broader organizational context. Practical implications emphasize the need for multinational firms to design adaptive, fair, and comprehensive compensation policies to enhance expatriate satisfaction and overall assignment effectiveness.